Phytofabrication, characterization of silver nanoparticles using Hippophae rhamnoides berries extract and their biological activities - Rana, Neha; Banu, A. Najitha; Kumar, Bimlesh; Singh, Sandeep K.; Abdel-razik, Noha E.; Jalal, Naif A.; Bantun, Farkad; Vamanu, Emanuel; Singh, Mahendra P. (Frontiers in Microbiology, 2024)
Introduction Fabrication of plant-based metal nanoparticles has yielded promising results, establishing this approach as viable, sustainable, and non-toxic in the biomedical sector for targeted drug delivery, diagnostic imaging, biosensing, cancer therapy, and antimicrobial treatments. Methods The present work demonstrates the suitability of Hippophae rhamnoides berries for the instant green synthesis of silver nanoparticles to check their antioxidant, lipid peroxidation, and antimicrobial potential. The preliminary characterization of Hippophae rhamnoides-mediated AgNPs was validated by monitoring the color shift in the solution from pale yellow to reddish brown, which was further confirmed by UV–vis spectroscopy and the plasmon peaks were observed at 450 nm. Field Emission Scanning Electron Microscopy (FESEM) and X-ray diffraction (XRD) were used to evaluate the surface topography and structure of AgNPs. Herein, the antioxidant potential of synthesized AgNPs was investigated using DPPH free radical assay and the antimicrobial efficacy of similar was checked against E. coli and S. aureus by following MIC (minimum inhibitory concentration) and MBC (Minimum bactericidal concentration) assay. Along with the inhibitory percentage of lipid peroxidation was analysed by following TBARS (Thiobarbituric acid reactive species) assay. Results & discussion The results revealed that the AgNPs were spherical in shape with an average size distribution within the range of 23.5–28 nm and a crystalline structure. Negative zeta potential (−19.7 mV) revealed the physical stability of synthesized AgNPs as the repulsive force to prevent immediate aggregation. The bioactive functional moieties involved in reducing bulk AgNO3 into AgNPs were further validated by FTIR. TBARS was adapted to test lipid peroxidation, and Hippophae rhamnoides-mediated AgNPs showed a 79% inhibition in lipid peroxidation compared to Hippophae rhamnoides berries extract as 65%. Furthermore, the antibacterial tests showed 37 ± 0.01 mm and 35 ± 0.0132 mm, zones of inhibition against E. coli MTCC 1698 and S. aureus MTCC 3160 with MIC and MBC values of 1 mg/mL, respectively.